Comparison of Ondansetron with Doxylamine plus Pyridoxine for the Treatment of Nausea and Vomiting during Pregnancy - Adiba Khatoon, Halima Sadia, Sara Ahmad Qureshi, Musaarat Batool, Qurra Tul Ain, Saqib Hussain (Pakistan Journal of Medical & Health Sciences, 2026)
Introduction: Nausea and vomiting in pregnancy (NVP) impacts up to 80% of pregnant women and can considerably diminish quality of life. Despite the endorsement of doxylamine and pyridoxine as first-line treatment, a significant proportion of women encounter insufficient symptom management or unpleasant reactions. Ondansetron has surfaced as a plausible option; yet, comparison data are still few, especially in outpatient contexts. Objective: To evaluate the effectiveness and safety of oral ondansetron against doxylamine combined with pyridoxine in the management of moderate to severe nausea and vomiting in pregnancy (NVP). Materials and Methods: This randomized controlled experiment was performed in Mother & Child Healthcare Center (MCHC), Pakistan Institute of Medical Sciences, Islamabad from June 4, 2021 to December 4, 2021. One hundred twenty-six pregnant women with a gestational age of less than 16 weeks and a PUQE score exceeding 6 were randomized into two groups. Group A was administered oral ondansetron, whereas Group B was given doxylamine in conjunction with pyridoxine for a duration of five days. The severity of symptoms was evaluated using the PUQE score at baseline and on day five. Results: The baseline features were similar among the groups. Ondansetron produced a much bigger decrease in PUQE ratings and a higher percentage of patients attaining ≥50% symptom relief in comparison to doxylamine–pyridoxine. The adverse effects were minor and similar across the groups. Conclusion: In conclusion, oral ondansetron demonstrates superior efficacy compared to: doxylamine + pyridoxine in managing moderate to severe nausea and vomiting in pregnancy, while maintaining a comparable safety profile. Keywords: Nausea and vomiting in pregnancy, ondansetron, doxylamine, pyridoxine, PUQE score